2020
DOI: 10.1073/pnas.2010984117
|View full text |Cite
|
Sign up to set email alerts
|

Curtailing FGF19’s mitogenicity by suppressing its receptor dimerization ability

Abstract: As a physiological regulator of bile acid homeostasis, FGF19 is also a potent insulin sensitizer capable of normalizing plasma glucose concentration, improving lipid profile, ameliorating fatty liver disease, and causing weight loss in both diabetic and diet-induced obesity mice. There is therefore a major interest in developing FGF19 as a therapeutic agent for treating type 2 diabetes and cholestatic liver disease. However, the known tumorigenic risk associated with prolonged FGF19 administration is a major h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…In parallel experiments, we administered mFGF4 and rFGF19 as positive controls; in both cases, these proteins are known to induce full proliferative activity 2 , 4 , 37 . Consistent with published literature 38 , 39 , rFGF19 treatment led to dramatic increase in the expression of hepatic proliferation markers (Supplementary Fig. 10j, k ).…”
Section: Resultssupporting
confidence: 91%
“…In parallel experiments, we administered mFGF4 and rFGF19 as positive controls; in both cases, these proteins are known to induce full proliferative activity 2 , 4 , 37 . Consistent with published literature 38 , 39 , rFGF19 treatment led to dramatic increase in the expression of hepatic proliferation markers (Supplementary Fig. 10j, k ).…”
Section: Resultssupporting
confidence: 91%
“…The 3D structure of the FGF23-FGFR1c complex determined by X-ray crystallography revealed it requires an obligatory interaction with KLα and heparan sulfate (HS) for a 1:1:1:1 assembly for signaling [ 144 ]. Based on these data and biochemical evidence of FGF19 signaling accumulated in the past [ 10 , 11 , 12 , 13 , 14 ], FGF15/19-FGFR4 also requires interaction with KLβ and HS for signaling with a 1:1:1:1 ratio [ 145 , 146 ]. Furthermore, FGF19 mutants with reduced dimerization potential elicit lower mitogenic activity accompanied with lower induced ERK1/2 phosphorylation, whereas hepatic Cyp7a1 expression reduced to similar levels as liver treated with WT [ 145 , 147 , 148 ].…”
Section: Regulation Production and Biological Function Of Fgf15/19mentioning
confidence: 99%
“…FGF family is divided into endocrine FGFs and paracrine FGFs, and endocrine type FGF19/21 has been widely studied in the field of metabolism. Mounting evidence showed that FGFs interact with FGFR in the 1:1 FGF-FGFR complex to facilitate FGF-FGFR dimerization, with increased intracellular receptor tyrosine kinase activity that triggers various downstream signaling pathways ( Huang et al, 2017 ; Zinkle and Mohammadi, 2018 ; Niu et al, 2020 ). So these endocrine/paracrine FGFs may also share the same mode of action and regulated the development of GDM.…”
Section: Discussionmentioning
confidence: 99%